Evaluation of antibacterial activity of Boesenbergia rotunda rhizome ethanolic extract and its potential as antibiotic adjuvant against human and plant pathogens - Ynion, Gene Philip Levee Q. (2019.)
The irresponsible and extensive use of antibiotics in treating infectious human and plant diseases has resulted to the spread of antimicrobial resistance. Human and plant infections caused by antibiotic resistance bacteria have now become a serious threat to public health and food security. Therefore, there is a great need to develop novel antibiotic compounds and/or to extend the efficacy of available antibiotic drugs through modification of its components to combat pathogenic microorganisms. This study aims to determine the antibacterial activity of Boesenbergia rotunda ethanolic extract against eight human pathogens and three plant pathogens, and study the antibiotic potentiating effect of the extract when added on standard antibiotic discs. The antibacterial activity of the extract was determined using disc-diffusion method. The extract and standard antibiotics were used alone and then combined, and the difference between the zones of inhibitions were obtained in order to determine whether there is a potentiating effect. Results showed that the plant extract was effective against S. marcescens, S. mutans, E. faecalis, P. syringae and S. aureus (ZOI: 14-20 mm). The extract greatly potentiated the effects of Erythromycin and Amoxicillin against S. mutans and B. subtilis, respectively. Antagonistic interactions were observed in most bacteria when the extract was combined with Levofloxacin and Gentamicin. However, the extract potentiated the effect of Levofloxacin and Gentamicin against M. luteus and E. coli, respectively. This study reveals that the extract is effective against several pathogens and is effective in potentiating the effects of some antibiotics in vitro.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2019.
Keywords: Boesenbergia rotunda; Rhizone Ethanolic Extract